Flexible thin-film rechargeable lithium battery - Ribeiro, J. F. (2013)
Flexible thin-film rechargeable lithium battery was fabricated only by PVD techniques. The Kapton® substrate provides flexibility to the battery and at the same time supports the depositions conditions inside the vacuum chamber. Platinum and titanium were deposited by e-beam and used as cathode and anode current collectors of the battery, respectively. LiCoO2 cathode was deposited by rf-sputtering with 150 W of power source, 40 sccm of Ar and 300 ºC in the substrate during deposition. The electrolyte LiPON was also deposited by rf-sputtering and the conditions explained before in J. F. Ribeiro, et al., [1]. The anode, lithium, was deposited with 3 μm thickness by thermal evaporation. The open circuit potential, Nyquist diagrams and charge/discharge capacity were used for battery characterization. The modelling of Nyquist equivalent circuit allowed calculating some battery parameters, like, internal resistance, battery charge resistance and battery effective diffusion coefficient. The equivalent circuit and the parameters were calculated with the help of Zview™ software.